(untitled) (Linguostylistic Studies, 2015)
The male proper names with initial Ш, Щ letters recorded in the lists of regiments of the Register of Zaporozhzhya Army of 1649 has been worked out lexicographically in the article. Their origin, phonetical and word formation changes have been considered, number of bearers of each name in the Register has been specified, use of name in other written memorials from old times to our time has been recorded. We see the history of the use of the name for centuries and geography functioning of name in all ethnic Ukrainian territories. Arises clear, distinct pattern of ethnic Ukrainian unity in the past century. The analysis makes it possible to see which variants of names remained as the official name, and which variants of names remained in modern folk anthroponymy. A large list of various phonetic and word-forming design surnames shows that often inconspicuous, rare nowadays spoken variant, in the past century has been an active and common almost everywhere. Key words: onomastics, Register of Zaporozhzhya Army of 1649, personal proper name, lexicography, phonetics, word formation. References